[George Gowgani in his office] (1990)
George Gowgani sits at his L shaped desk wearing a blazer and a shirt with a tie with a paper in his hand. He wears a watch with a dark face on his left hand. Placed on the desk is an office phone, various mugs, a pair of glasses, and a lot of paperwork. There is an office plant and framed portraits located on top of a full bookshelf behind where he is seated. There are three photographs and an official document framed and hanged on his wall.